Lucretia’S Motives a Philosophical Consideration on Rape and Self-Killing; [Los Motivos de Lucrecia. Una Consideración Filosófica Sobre la Violación y el Darse Muerte] - Neira-Barrera, H (Universidad Nacional de Colombia, 2023)
Lucretia narrates her rape and promptly commits suicide. Her act is private, but she joins it with another of public consequences; this act regards the State and it is also offered to public discussion. With this act, she transfers political responsibilities on the patricians and awakes public duties on them. Agustin of Hippo’s and Kant’s analysis on that suicide, centred on shame and honour, neglects the relevance of testify and making known the crime, do not glimpse the chain of moral and political deeds that Lucretia enlightens and they do not discern the public interest of the fact. A philosophical consideration about narrating rape and suicide allows elucidating some political acts of the heroine and of rape. © 2023 Universidad Nacional de Colombia. All rights reserved.